IMPLEMENTASI SELF DIRECT LEARNING UNTUK MENINGKATKAN KREATIVITAS BELAJAR FIKIH DI MTS NURUL FALAH JOKARTO - Al Fajri, Yusron (Universitas Nahdlatul Ulama Surakarta, 2024)
This study aims to determine and evaluate the application of the Self Direct Learning model in improving the learning creativity of ninth grade fiqh students at MTs nurul falah jokarto. This research uses a qualitative-descriptive method. Data collection techniques using in-depth interviews, observation, and documentation. The results of this study are: 1) The learning process of fiqh class IX subjects at Mts Nurul Falah Jokarto uses a varied Learning Model, one of which is the Self Direct Learning model. 2) The application of the Self Direct Learning model can increase the learning creativity of ninth grade fiqh students at Mts Nurul Falah Jokarto